Comparison of coconut water and a carbohydrate-electrolyte sport drink on measures of hydration and physical performance in exercise-trained men - Kalman, D. S.; Feldman, S.; Krieger, D. R.; Bloomer, R. J. (Journal of the International Society of Sports Nutrition, 2012)
Sport drinks are ubiquitous within the recreational and competitive fitness and sporting world. Most are manufactured and artificially flavored carbohydrate-electrolyte beverages. Recently, attention has been given to coconut water, a natural alternative to manufactured sport drinks, with initial evidence indicating efficacy with regard to maintaining hydration. We compared coconut water and a carbohydrate-electrolyte sport drink on measures of hydration and physical performance in exercise-trained men. Methods: Following a 60- minute bout of dehydrating treadmill exercise, 12 exercise-trained men (26.6+/-5.7 yrs) received bottled water (BW), pure coconut water (VitaCoco(R): CW), coconut water from concentrate (CWC), or a carbohydrate-electrolyte sport drink (SD) [a fluid amount based on body mass loss during the dehydrating exercise] on four occasions (separated by at least 5 days) in a random order, single blind (subject and not investigators), cross-over design. Hydration status (body mass, fluid retention, plasma osmolality, urine specific gravity) and performance (treadmill time to exhaustion; assessed after rehydration) were determined during the recovery period. Subjective measures of thirst, bloatedness, refreshed, stomach upset, and tiredness were also determined using a 5-point visual analog scale. Results: Subjects lost approximately 1.7 kg (~2% of body mass) during the dehydrating exercise and regained this amount in a relatively similar manner following consumption of all conditions. No differences were noted between coconut water (CW or CWC) and SD for any measures of fluid retention (p>0.05). Regarding exercise performance, no significant difference (p>0.05) was noted between BW (11.9+/-5.9 min), CW (12.3+/-5.8 min), CWC (11.9+/-6.0 min), and SD (12.8+/-4.9 min). In general, subjects reported feeling more bloated and experienced greater stomach upset with the CW and CWC conditions. Conclusion: All beverages are capable of promoting rehydration. Little difference is noted 3 between the four tested conditions with regard to markers of hydration or exercise performance in a sample of young, healthy men. Additional study inclusive of a more demanding dehydration protocol, as well as a time trial test as the measure of exercise performance, may more specifically determine the efficacy of these beverages on enhancing hydration and performance following dehydrating exercise.